Long-Term Outcomes in Primary Obstructive Megaureter Treated by Endoscopic Balloon Dilation. Experience After 100 Cases - Ortiz, Ruben; Parente, Alberto; Perez-Egido, Laura; Burgos, Laura; Angulo, José Maria (Frontiers in Pediatrics, 2018)
Aim: to assess long-term effectiveness, complications and outcomes of primary obstructive megaureter (POM) treated by endoscopic balloon dilation (EBD) in the largest series reported. Patients and methods: 100 POM in 92 consecutive patients were treated by EBD between years 2004-2016. A total of 79 POM (73 patients) with more than 18 months of follow-up after treatment have been analyzed. EBD of the vesicoureteral junction was performed with semicompliant high-pressure balloon catheters (2.7FG) with minimum balloon diameter of 5mm, followed by temporary Double-J stent placement. Follow-up protocol included periodical clinical reviews, US and MAG-3 renogram scans. Results: Median age at surgery was 4 months (15 days-3.6 years), with median operating time of 20 minutes (10-60) and hospital stay of 1 day (1-7). Initial renal function was preserved in all patients with significant improvement in renal drainage on the MAG-3 diuretic renogram after endoscopic treatment (p<0.001 T-test). Significant postoperative differences were observed in hydronephrosis grade and ureteral diameter that were maintained in the long-term (p<0.001 T-test). Endoscopic approach of POM had a long-term success rate of 87.3%, with a mean follow-up of 6.4±3.8 years. Secondary VUR was found in 17 cases (21.5%), being successfully treated by endoscopic subureteral injection in 13 (76,4%). Nine cases developed long-term re-stenosis (12.2%) that were successfully treated with a new EBD in 8. Endoscopic management of POM failed in 10 cases (12.7%) that required ureteral reimplantation. Five were early failures (4 intraoperative technical problems and 1 double-J stent migration with severe re-stenosis), and 5 long-term (4 persistent VUR and 1 re-stenosis recurrence). Conclusion: EBD has shown to be an effective treatment of POM with few complications and good outcomes at long-term follow up. Main complication was secondary VUR that could also be treated endoscopically with a high success rate. In our opinion, EBD may be considered first-line treatment in POM.